Decor(at)i(o)n: less is more? - Trogisch, Felix; Heineke, Jörg (Cardiovascular research, 2025)
This editorial refers to ‘Ageing-associated endothelial decorin induction and the impact of non-glycanated decorin on cardiac inflammation’ by G. Luxán et al., https://doi.org/10.1093/cvr/cvaf128.Ageing strongly contributes to cardiovascular morbidity and mortality. The majority of cardiac conditions that result in systolic heart failure are caused either by acute injuries, such as myocardial infarction (MI), or by prolonged haemodynamic overload, as seen in valve disorders. In contrast, ageing reflects a more complex situation, in which multiple hallmarks promote disease with an impairment of diastolic function as most prominent feature.1 Myocardial changes observed in ageing range from left atrial enlargement, left ventricular stiffening, thickening of the left ventricular wall and cardiac fibrosis to mitochondrial dysfunction.2 As the population of elderly cardiovascular patients grows, the need for treatments targeting age-related heart failure is steadily increasing.